Psychological Exploitation of Pregnant Women During the Covid-19 Pandemic - Miskiyah Miskiyah; Nia Clarasari Mahalia Putri (International Journal Scientific and Professional (IJ-ChiProf), 2022)
The spread of COVID-19 globally impacts individuals' fear, stress, and anxiety. This trend is increasing, especially in pregnant women because it belongs to the group at risk to the safety of themselves and their fetuses. This study explores pregnant women's concerns, problems, and attitudes regarding the condition of the outbreak of Covid-19 during the pandemic through detailed and directed discussions based on their respective experiences to be a benchmark for antenatal services by midwives. Method: Data in analysis with qualitative studies. The interview was conducted on 14 pregnant women in Muara Enim Regency of South Sumatra via mobile phone due to social isolation regulations during the Covid-19 pandemic. The result of the analysis of interview content is processed with ten themes, namely: (1) negative emotional states, (2) living with uncertainty (3) changes in routine and social life. (4) concerns about infection, (5) the use of complementary therapies, (6) social support, (7) financial and occupational issues, (8) concerns about birth, (9) antenatal and postnatal services (10) Unclear information. This study shows that the Covid-19 pandemic caused various difficulties, anxiety, and fear, giving rise to various psychological changes in pregnancy. Midwives as antenatal service providers can make the results of this study to modify the special antenatal services of pandemic Covid-19. The service not only focuses on the physical but also prepares the mental health of pregnant women. Collaboration with other health teams becomes necessary to maintain the condition of maternal pregnancy during the Covid-19 Pandemic.